EXPLORING THE RELATIONSHIP BETWEEN WORD KNOWLEDGE AND EFFECTIVE COMMUNICATION - Putu Sri Astuti (Jurnal Cakrawala Ilmiah, 2023)
Many studies have explored strategies to master word knowledge and communication in English as a Foreign Language (EFL), but only a few have yielded satisfying findings regarding the correlation between these two domains. This research aimed to investigate the significant correlation between English word knowledge proficiency and communication skills. An Ex Post Facto research design was employed, involving a sample of 40 students selected from a total of 150 students at SMK PGRI 3 Badung. Tests were administered to measure the variables, and the data were analyzed using SPSS 25.0 to determine the correlation between English word knowledge mastery and communication skills. The results indicated a significant positive correlation between students' English word knowledge proficiency and their communication skills. These findings imply that a higher level of word knowledge mastery is associated with enhanced communication abilities, highlighting the importance of word knowledge acquisition in facilitating effective communication.